Perception of students from a school in an urban environment of the impact of rural fires on society, the territory, and the environment - Borges, Marília Correia (2021)
The theme of rural fires is addressed in the subject of geography in the 9th year of schooling, in regular education. For this reason, it is pertinent to reflect on how this might influence the awareness and co-responsibility of students. The main objective of this research was to encourage students to reflect on and analyse their perception of the impacts of rural fires on society, territory, and the environment. The methodology had two stages; the students first performed a diagnostic test, which was provided through the Socrative tool, and then they carried out a group survey in which each group selected and analysed a district and the respective analysis parameters developed in the work guide. Overall, it was found that the students' perception surpassed the initial expectations, since they identified the impacts at an environmental and territorial level. However, in relation to the social level the students showed a certain lack of knowledge. Our research was carried out at Colégio Nossa Senhora de Lourdes in the municipality of Porto.